Pharmacological evaluation of “Glyoherb”: A polyherbal formulation on streptozotocin-induced diabetic rats - Thakkar, Nima V. (Medknow Publications, 2010)
In the present study, powdered suspension of ‘Glyoherb’- sugar control granules, a polyherbal formulation (manufactured by Dhanvantri Guj. herb., Valasan, Anand, Gujarat, India) was evaluated for its antihyperglycemic, antihyperlipidemic and antioxidant effects against normal and streptozotocin-induced diabetic rats. Type I diabetes was induced when streptozotocin 70 mg/kg was administered as a single i.p. injection. After five days of streptozotocin injection, animals showing glycosuria (fasting blood sugar level >200 mg/dl) were considered as diabetic. Daily oral administration of ‘Glyoherb’ suspension in 200, 400 and 600 mg/kg doses for 28 days produced a dose-dependant decrease in blood glucose levels. It also produced a significant decrease in elevated serum triglyceride, cholesterol, VLDL, LDL, atherogenic index, serum urea, and creatinine and in antioxidant parameters in a dose dependant manner. Results were analyzed using one way ANOVA followed by Tukey's test. No significant changes were noticed in blood glucose, serum lipid levels and kidney parameters in normal rats treated with ‘Glyoherb’ suspension alone. The efficacy of ‘Glyoherb’ suspension as an antihyperglycemic, antihyperlipidemic and antioxidant agent in streptozotocin-induced diabetes was comparable to that of the standard drug Glibenclamide (5 mg/kg).